Femicide : problems, possibilities, and prevention - Fitz-Gibbon, Kate; Walklate, Sandra (Emerald studies in criminology, feminism and social change., 2025)
Femicide - the killing of women and girls - has gained increasing prominence on global and national agendas since the United Nations and the World Health Organisation, amongst others, started to respond to femicide as an issue of global concern. This edited collection explores the nature and extent of femicide, from intimate partner femicide to its connections with women's suicide, and the institutional failures associated with Indigenous women's deaths in the context of intimate partner violence. This collection contributes to progressing Sustainable Development Goal (SDG) 5.2.1: the elimination of all forms of violence against women and girls in public and in private, which sits within SDG5 focused on improving gender equality worldwide. In extending recent work done by the editors on the measurement of women's deaths as a result of male violence, Femicide: Problems, Possibilities and Prevention considers how theory, research, activism, policy, and prevention in different contemporary environments impact on how femicide is defined, understood and prevented. The debates explored within this book pose particular challenges for practitioners in developing effective risk informed prevention.